Agrobacterium-mediated gene delivery and transient expression in the red macroalga Chondrus crispus - Ramessur, Anusha Devi; Bothwell, John H.; Maggs, Christine A.; Gan, Sook Yee; Phang, Siew Moi (De Gruyter, 2018)
Molecular resources and transgenic studies in red algae are lagging behind those for green algae. The Agrobacterium-mediated gene-transfer method routinely used in plant transformation has not been fully utilised in the red algae, which, as an important source of phycocolloids, warrant more studies. In this regard, a stepwise methodology was developed for Agrobacterium-mediated transformation of the carrageenophyte Chondrus crispus using pCAMBIA 1301 and a construct featuring a codon-optimized beta-glucuronidase (GUS) reporter gene driven by the endogenous Chondrus actin promoter. The effects of several factors on transformation efficiency were investigated. An intimate association of Chondrus and bacterial cells was observed using scanning electron microscopy. GUS transient expression within Chondrus cortical and medullary cells with both expression cassettes testified to the amenability of Chondrus to Agrobacterium-mediated transformation. Darker staining, indicative of higher GUS activity, was observed with the Chondrus-specific construct, suggesting its superiority over the pCAMBIA 1301. Presence of acetosyringone, the wounding method and the type of co-cultivation medium significantly affected the transformation outcome and efficiency. The Agrobacterium-mediated transient expression presented here constitutes a first step towards tailoring a transformation strategy for Chondrus, which can serve to facilitate further transgenic studies in this important red alga.